Helical ordering of envelope‐associated proteins and glycoproteins in respiratory syncytial virus. (22nd December 2021) - Conley, Michaela J; Short, Judith M; Burns, Andrew M; Streetley, James; Hutchings, Joshua; Bakker, Saskia E; Power, B Joanne; Jaffery, Hussain; Haney, Joanne; Zanetti, Giulia; Murcia, Pablo R; Stewart, Murray; et al.
Abstract: Human respiratory syncytial virus (RSV) causes severe respiratory illness in children and the elderly. Here, using cryogenic electron microscopy and tomography combined with computational image analysis and three‐dimensional reconstruction, we show that there is extensive helical ordering of the envelope‐associated proteins and glycoproteins of RSV filamentous virions. We calculated a 16 Å resolution sub‐tomogram average of the matrix protein (M) layer that forms an endoskeleton below the viral envelope. These data define a helical lattice of M‐dimers, showing how M is oriented relative to the viral envelope. Glycoproteins that stud the viral envelope were also found to be helically ordered, a property that was coordinated by the M‐layer. Furthermore, envelope glycoproteins clustered in pairs, a feature that may have implications for the conformation of fusion (F) glycoprotein epitopes that are the principal target for vaccine and monoclonal antibody development. We also report the presence, in authentic virus infections, of N‐RNA rings packaged within RSV virions. These data provide molecular insight into the organisation of the virion and the mechanism of its assembly. Synopsis: CryoEM and tomography analysis of the human pathogen respiratory syncytial virus shows the formation of filamentous virions that exhibit helical ordering of the envelope associated matrix protein layer, which in turn coordinates helical ordering and clustering of viral glycoproteins. 16 Å resolution sub‐tomogram average of the matrix protein (M) layer that forms an endoskeleton below the viral envelope. Respiratory syncytial virus filamentous virions have a helically ordered matrix layer that is formed by a lattice of M dimers. Viral glycoproteins embedded in the envelope also show helical ordering and frequently cluster in pairs, these properties are coordinated by the underlying matrix layer. In addition to packing multiple copies of the viral genome in the form of helical ribonucleoprotein complexes or nucleocapsids, virions also package an abundance of ring‐shaped assemblies likely formed of the viral nucleocapsid protein (N) and RNA. Abstract : CryoEM and tomography analysis of the human pathogen RSV shows the formation of filamentous virions that exhibit helical ordering of the envelope associated matrix protein layer that in turn coordinates helical ordering and clustering of viral glycoproteins.